2018
DOI: 10.3354/meps12501
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of stability of rhodolith beds: sedimentological aspects

Abstract: Rhodolith beds are highly diverse benthic communities organized around the physical structure and primary productivity of red coralline algae. Despite a worldwide distribution and growing recognition that rhodolith beds are important calcium carbonate (CaCO3) biofactories, little is known of the factors and processes that regulate their structure, function, and stability. One prevalent and largely untested paradigm is that beds develop in environments where water motion is strong enough to prevent burial by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 108 publications
2
16
0
Order By: Relevance
“…The optimum conditions for rhodolith growth might be due to a flatter seafloor between 15 and 20 m (Figure 1). Despite the weak current perceived, the highest proportion of very fine sand and mud occurs at 18 m. This can be due to the well-known baffling effect of dense concentrations of branching rhodoliths, which stabilize fine-grained sediment below them (Bassi et al, 2009;Millar and Gagnon, 2018;O'Connell et al, 2021).…”
Section: Discussion Bed Structure and Rhodolith Characteristicsmentioning
confidence: 99%
“…The optimum conditions for rhodolith growth might be due to a flatter seafloor between 15 and 20 m (Figure 1). Despite the weak current perceived, the highest proportion of very fine sand and mud occurs at 18 m. This can be due to the well-known baffling effect of dense concentrations of branching rhodoliths, which stabilize fine-grained sediment below them (Bassi et al, 2009;Millar and Gagnon, 2018;O'Connell et al, 2021).…”
Section: Discussion Bed Structure and Rhodolith Characteristicsmentioning
confidence: 99%
“…Water motion, such as waves and currents, has been indicated as the main responsible for maintaining the rhodoliths unburied [16][17][18][19], and rhodoliths are often associated with sedimentary structures, such as ripple marks and dunes [19][20][21][22]. Some authors demonstrated that rhodoliths do not need to be exposed to threshold hydrodynamic forces to avoid burial [23,24], suggesting a primary role of bioturbation [23,25]. Despite this, rhodoliths are often associated with sedimentary structures, such as ripple marks and dunes [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between rhodolith outer/inner structure and water energy/water depth is debated in the literature, and no straightforward interpretation can be drawn. Moreover, only qualitative indications on velocity and frequency of current related to specific shape or morphotype have been provided thus far, included both field measurements, experimental models, and tanks [6,23,24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively complex morphology of rhodoliths creates suitable habitats for attachment (Kamenos et al, 2004a;Steller and Cáceres-Martínez, 2009;Riosmena-Rodríguez and Medina-López, 2010), reproduction (Kamenos et al, 2004b;Steller and Cáceres-Martínez, 2009;Gagnon et al, 2012), and feeding (Steneck, 1986;Gagnon et al, 2012;Riosmena-Rodríguez et al, 2017) of highly diverse algal and faunal assemblages. The important contribution of rhodolith beds to marine biodiversity (Steller et al, 2003;Gagnon et al, 2012;Riosmena-Rodríguez et al, 2017) and global calcium carbonate (CaCO 3 ) production (Amado-Filho et al, 2012;Harvey et al, 2017;Teed et al, 2020) has, in part, triggered the recent increase in studies of factors and processes regulating their structure and function (Marrack, 1999;Hinojosa-Arango et al, 2009;Millar and Gagnon, 2018) and growth resilience to natural and anthropogenic stressors (Bélanger and Gagnon, 2020;Bélanger and Gagnon, 2021;Arnold et al, 2021) Knowledge about trophodynamics in rhodolith beds is limited to only a couple of studies in northeastern Atlantic (Grall et al, 2006) and eastern Pacific (Gabara, 2014) systems, that together suggest suspended particulate organic matter (SPOM), sediment organic matter (SOM), and macroalgae are important components of rhodolith bed food webs. Both studies' findings are based on use of bulk stable isotope analysis, in particular consideration of organisms' carbon (δ 13 C) and nitrogen (δ 15 N) isotopic signatures (DeNiro and Epstein, 1978;DeNiro and Epstein, 1981;Minagawa and Wada, 1984) to identify primary producers (Peterson and Fry, 1987;Post, 2002;Bouillon et al, 2011) and trophic levels of consumers…”
Section: Introductionmentioning
confidence: 99%